APPLICATION OF HUMAN RESOURCE MANAGEMENT IN IMPROVING TEACHER COMPETENCE - Rizqi, Miftahur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The study resulted of field study in MA Darut Tauhid about the management of human resources in improving teacher competence there. The study aims to answer the academic problem of knowing the application of human resource management in improving teacher competence and to know the factors and impediments to improving teacher competence. A method used qualitatively descriptively with the string of phenomena, its data collection techniques by observing, deep interviews, and documentaries, the data analysis used is data reduction, data presentation, and conclusion retrieval, and data recon using data triangulation. The results of this study are that: 1) the application of human resource management in maximizing teacher competence begins with planning, organization, direction, and control; 2) the inclusion factor includes the support of the parents; and 3) teachers are included in a training program. The retard factor is a lack of discipline, so that human resource management professionals are as limited as the means and infrastructure that can impede the teaching and learning.